Spatial Disaster Risk Assesment of Kelud Eruption, Indonesia, using Fuzzy - Titis Octary Satrio; Arna Fariza; Mu'arifin Mu'arifin (Politeknik Negeri Padang, 2019)
Indonesia is one of the countries included in the area of the Ring of Fire or the Ring of the Pacific. This fact can be seen that in Indonesia there are 129 active volcanoes and 10 of them are the most active volcanoes. Mount Kelud is the most active volcano in the province of East Java, Indonesia. This mountain is recorded as actively erupting with a relatively short span of time (9-25 years), making it a volcano that is dangerous for humans. Readiness of citizens is very necessary as an effort to prevent and anticipate the eruption of Mount Kelud in the future. Disaster risk level assessments are needed to provide information for citizen and government preparedness in the face of volcanic eruptions. In this paper a new approach is proposed to assess the level of disaster risk of Kelud eruption using Fuzzy methods in each village in the disaster-prone area (KRB). Fuzzy methods classify disaster risk levels based on criteria of hazards, vulnerabilities and index of capacities. The level of disaster risk is divided into low, medium, and high which are spatially mapped. The result of calculations and spatial visualization show that the approach used produces a level of disaster risk that is fairer than only based on hazard.